Entornos virtuales y su incidencia en la interacción didáctica con estudiantes de EGB en la Parroquia Febres Cordero del cantón Babahoyo 2024–2025 - Figueroa Navarrete, Lissy Mishelle (2025)
The application of virtual environments in the academic context in recent years has had vital relevance due to the various benefits it generates to the learning-teaching process of students, especially today. Based on the objective, it has been established to determine the incidence of the use of virtual environments in the didactic interaction with EGB students in the Febres Lamb parish of the Babahoyo canton. In the methodology, exploratory research was applied, given that the level of analysis will not be in-depth, it will only seek to determine the incidence and impact of the application of virtual environments to generate knowledge in a specific group of Basic General Education students. in the Febres Cordero Parish of the Babahoyo Canton. Based on the results, the overall participation average needs to be improved since a quarter of the students show zero involvement, which could generate a negative impact on the learning process in a virtual environment. In conclusion, the use of virtual environments in the students of the Febres Cordero parish has had a positive impact in terms of didactic interaction between which its efficiency is determined, which depends on the accessibility to technology, the training of the teachers and the level of familiarity of the students with the technological platforms at the time of receiving virtual classes.